A comparative study of tualang honey hydrogel with safecare hydrogel dressing in the treatment of split-skin graft donor sites - Farrah Hani, Imran (2010)
Hydrogel is a well established wound dressing. This study looks at the benefits conferred when Tualang Honey is added to plain hydrogel (Safecare Hydrogel). A randomized prospective study was performed to investigate and compare the healing properties of Safecare Hydrogel and Honey Hydrogel with regards to their healing of split skin graft donor sites. Patients who underwent split skin grafting were screened for this study. Those who met the inclusion and exclusion criteria qualified for the study. These patients were recruited from the patient population in Hospital Universiti Sains Malaysia (HUSM) over a period of 18 months. Individual written consent for inclusion in this study was obtained from each patient. Using simple randomisation, 70 patients were assigned into 2 groups, 35 patients received commercially available Safecare Hydrogel dressing and 35 received Honey Hydrogel dressing applied to their split skin graft donor sites. All donor sites are inspected on the lOth, 15th and 20th post-operative day. The parameters assessed are wound healing rates and pain assessment. There was a difference observed in both these parameters between both groups. The rate of healing of the wounds were found to be faster in the Honey Hydrogel group and caused less pain, discomfort and pruritus, requiring less analgesia when compared with the Safecare Hydrogel group. Honey Hydrogel is highly effective in the treatment of split-skin graft donor sites. The difference is clinically significant and reflects potential cost reduction in terms of reduced duration of hospital stay and increased level of comfort for the patient.